2018
DOI: 10.1007/s11920-018-0916-9
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advancements in Treating Sleep Disorders in Co-Occurring PTSD

Abstract: PTSD treatments decrease PTSD severity and nightmare frequency, but do not resolve OSA or insomnia. Research on whether insomnia hinders PTSD treatment shows mixed results; untreated OSA does interfere with PTSD treatment. Cognitive behavioral therapy for insomnia is the recommended treatment for insomnia; however, optimal ordering with PTSD treatment is unclear. PTSD treatment may be most useful for PTSD-related nightmares. CPAP therapy is recommended for OSA but adherence can be low. Targeted treatment of sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 146 publications
(168 reference statements)
0
57
1
1
Order By: Relevance
“…There is preliminary evidence for the efficacy of cognitive behavioural therapy for insomnia (CBT-I) as an effective intervention in psychiatric populations (Wu, Appleman, Salazar, & Ong, 2015 ). It is currently recommended as the best treatment option for sleep disturbance in PTSD (Colvonen et al, 2018 ; Miller, Brownlow, & Gehrman, 2020 ); however, it has not received significant attention in this context (Taylor & Pruiksma, 2014 ) and the optimal ordering with treatment for the waking symptoms of PTSD, is unknown (Colvonen et al, 2018 ). Preliminary studies of integrated treatment approaches that target both sleep and other symptoms of PTSD have shown promise (Colvonen, Drummond, Angkaw, & Norman, 2019 ; Miller et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is preliminary evidence for the efficacy of cognitive behavioural therapy for insomnia (CBT-I) as an effective intervention in psychiatric populations (Wu, Appleman, Salazar, & Ong, 2015 ). It is currently recommended as the best treatment option for sleep disturbance in PTSD (Colvonen et al, 2018 ; Miller, Brownlow, & Gehrman, 2020 ); however, it has not received significant attention in this context (Taylor & Pruiksma, 2014 ) and the optimal ordering with treatment for the waking symptoms of PTSD, is unknown (Colvonen et al, 2018 ). Preliminary studies of integrated treatment approaches that target both sleep and other symptoms of PTSD have shown promise (Colvonen, Drummond, Angkaw, & Norman, 2019 ; Miller et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, interventions promoting restful sleep in the immediate aftermath of trauma may bear the potential to reduce the risk for PTSD. Although promising, sleep-based interventions such as cognitive behavioral therapy for insomnia have rarely been investigated as preventive treatment after trauma (Colvonen et al, 2018). The current state of research underscores that such investigations are both timely and warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found difficulty in sleep onset and maintenance to be the most frequently reported symptom of posttraumatic stress disorder (PTSD; e.g., Pruiksma et al, 2016). Upwards of 90% of individuals with PTSD report difficultly sleeping and 35–61% of individuals with PTSD meet diagnostic criteria for insomnia (Colvonen et al, in press). Insomnia severity is associated with greater severity of PTSD symptoms, poorer quality of life, and worse daily functioning (e.g., Martindale, Morissette, Rowland, & Dolan, 2017; Morgan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Insomnia severity is associated with greater severity of PTSD symptoms, poorer quality of life, and worse daily functioning (e.g., Martindale, Morissette, Rowland, & Dolan, 2017; Morgan et al, 2017). Reviews of studies that examine sleep during PTSD treatment suggest that while sleep does improve over the course of successful PTSD treatment, upwards of 80% still report clinically significant insomnia following treatment (Colvonen et al, in press). This is particularly concerning given that there are converging lines of evidence suggesting that insomnia may compromise underlying mechanisms used in trauma-focused PTSD treatment (e.g., Belleville, Guay, & Marchand, 2011; Gutner, Casement, Gilbert, & Resick, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation